Allogeneic hematopoietic stem cell transplantation at the first remission for younger adults with FLT3‐internal tandem duplication AML: The JALSG AML209‐FLT3‐SCT study. Issue 7 (29th May 2020) - Kawashima, Naomi; Ishikawa, Yuichi; Atsuta, Yoshiko; Sawa, Masashi; Ozawa, Yukiyasu; Hayashi, Masaki; Kohno, Akio; Tomita, Akihiro; Maeda, Tomoya; Sakaida, Emiko; Usuki, Kensuke; Hagihara, Maki; et al.
Abstract: In this phase II multicenter study (JALSG AML209‐FLT3‐SCT), we aimed to prospectively elucidate the role of allogeneic hematopoietic stem cell transplantation (allo‐HSCT) at first complete remission (CR1) for FLT3 ‐internal tandem duplication (ITD)‐positive AML. Newly diagnosed de novo AML patients with FLT3 ‐ITD were enrolled at the achievement of CR1 and received allo‐HSCT as soon as possible after the first consolidation therapy. Mutations of 57 genes in AML cells at diagnosis were also analyzed. Among 48 eligible patients with a median age of 38.5 (17‐49) years, 36 (75%) received allo‐HSCT at a median of 108 days after CR1. The median follow‐up was 1726 days. The primary end‐point, 3‐year disease‐free survival (DFS) based on an intent to treat analysis, was 43.8% (95% confidence interval [CI], 30%‐57%), suggesting the efficacy of this treatment because the lower limit of the 95% CI exceeded the threshold response rate of 20%. The 3‐year overall survival, post‐transplant DFS, and non‐relapse mortality rates were 54.2% (95% CI, 39%‐67%), 58.3% (95% CI, 41%‐72%), and 25.0% (95% CI, 12%‐40%), respectively. The median ITD allelic ratio (AR) was 0.344 (0.006‐4.099). Neither FLT3 ‐ITD AR nor cooccurring genetic alterations was associated with a poor DFS. This prospective study indicated the efficacy and safety of allo‐HSCT for FLT3‐ ITD AML patients in CR1. This study was registered at: www.umin.ac.jp/ctr/ as #UMIN000003433. Abstract : Kaplan‐Meier estimates of disease‐free survival (A) and overall survival (B) in 48 AML patients with FLT3 internal tandem duplication.